Ketimpangan Pena Jurnalis atas Kriminalisasi Kemerdekaan dan Kebebasan Pers - Habibie, Mohammad Ahsan; Michael, Tomy (CV. Era Digital Nusantara, 2025)
The purpose of this study is to examine factually and practically the imbalance of rights and obligations for journalists due to the criminalization of press freedom, as stipulated in Law Number 19 of 2016 concerning Electronic Information and Transactions, which has been amended to Law Number 1 of 2024 concerning Electronic Information and Transactions (Law Number 1/ 2024), as well as other relevant laws and regulations. Through this research, an in-depth discussion will be conducted regarding the legal impact of criminalization on the press and the necessity of regulations that protect press freedom from criminalization. Additionally, it emphasizes the need for a review and revision of Law Number 1/ 2024 and Law Number 40 of 1999 concerning the Press (Law Number 40/ 1999). This study employs a normative legal research method, incorporating conceptual and legislative approaches, based on primary, secondary, and tertiary legal sources relevant to the issue. Legal reasoning is also applied in this research. The findings indicate that legal protection efforts against the criminalization of the press are still necessary, as there are still journalistic activities that may harm others.